Efficacy and safety of combination therapy with pramipexole and levodopa vs levodopa monotherapy in patients with Parkinson disease: A systematic review and meta-analysis. Issue 44 (5th November 2021) - Wang, Yan; Jiang, De-Qi; Lu, Cheng-Shu; Li, Ming-Xing; Jiang, Li-Lin
Abstract: Background: Pramipexole ( P ) or levodopa ( L ) treatment has been suggested as a therapeutic method for Parkinson disease (PD) in many clinical studies. Nonetheless, the combined effects of 2 drugs for PD patients are not completely understood. The aim of this research was to evaluate the clinical efficacy and safety of P plus L ( P + L ) combination therapy in the treatment of PD compared to that of L monotherapy, in order to confer a reference for clinical practice. Methods: Randomized controlled trials (RCTs) of P + L for PD published up to April, 2020 were retrieved. Standardized mean difference (SMD), odds ratio (OR), and 95% confidence interval (CI) were calculated and heterogeneity was measured with the I 2 test. Sensitivity analysis was also carried out. The outcomes of interest were as follows: the efficacy, unified Parkinson disease rating scale (UPDRS) scores, Hamilton depression rating scale score or adverse events. Results: Twenty-four RCTs with 2171 participants were included. Clinical efficacy of P + L combination therapy was significantly better than L monotherapy (9 trials; OR 4.29, 95% CI 2.78 to 6.64, P  < .00001). Compared with L monotherapy, the pooled effects of P + L combination therapy on UPDRS score were (22 trials; SMD −1.31, 95% CI −1.57 to −1.04, P  < .00001) for motor UPDRS score, (16 trials; SMD −1.26, 95% CI −1.49 to −1.03, P  < .00001) for activities of daily living UPDRS score, (12 trials; SMD −1.02, 95% CI −1.27 to −0.77, P  < .00001) for mental UPDRS score, (10 trials; SMD −1.54, 95% CI −1.93 to −1.15, P  < .00001) for complication UPDRS score. The Hamilton depression rating scale score showed significant decrease in the P + L combination therapy compared to L monotherapy (12 trials; SMD −1.56, 95% CI −1.90 to −1.22, P  < .00001). In contrast to L monotherapy, P + L combination therapy reduced the number of any adverse events obviously in PD patients (16 trials; OR 0.36, 95% CI 0.27 to 0.50, P  < .00001). Conclusions: P + L combination therapy is superior to L monotherapy for improvement of clinical symptoms in PD patients. Moreover, the safety profile of P + L combination therapy is better than that of L monotherapy. Further well-designed, multicenter RCTs needed to identify these findings.